2019
DOI: 10.1002/pat.4521
|View full text |Cite
|
Sign up to set email alerts
|

Mussel‐inspired decoration of Ni(OH)2 nanosheets on 2D MoS2 towards enhancing thermal and flame retardancy properties of poly(lactic acid)

Abstract: In the present work, a facile and environmental method was developed to fabricate the novel functionalized MoS2 hybrid. Firstly, MoS2 nanosheets were coated with polydopamine (PDA) through the self‐polymerization of dopamine (MoS2‐PDA) in a buffer solution. Then the decoration of Ni(OH)2 on the MoS2‐PDA was synthesized because of the strong affinity of Ni2+ with hydroxyl groups in PDA. Finally, the as‐synthesized MoS2‐PDA@Ni(OH)2 was introduced into poly(lactic acid) (PLA) matrix to explore flame retardancy, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…19,24 MoS 2 NSs exhibited a 0.62 nm lattice spacing between layers, which is greater than that of graphene (0.335 nm), and later offered multifold improvement in the sensitivity of a biosensing platform. 25,26 Owing to the poor conductivity of MoS 2 NSs 27 and its fewer functionalities, 28 it would be an ideal approach to utilize the combination of other conducting nanomaterials such as noble metal nanoparticles, 29,30 transition metal oxides, [31][32][33] polymers, [34][35][36][37][38] metal-organic frameworks, 39 and porous coordination polymers 40 with MoS 2 NSs to prepare nanocomposites with enhanced conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…19,24 MoS 2 NSs exhibited a 0.62 nm lattice spacing between layers, which is greater than that of graphene (0.335 nm), and later offered multifold improvement in the sensitivity of a biosensing platform. 25,26 Owing to the poor conductivity of MoS 2 NSs 27 and its fewer functionalities, 28 it would be an ideal approach to utilize the combination of other conducting nanomaterials such as noble metal nanoparticles, 29,30 transition metal oxides, [31][32][33] polymers, [34][35][36][37][38] metal-organic frameworks, 39 and porous coordination polymers 40 with MoS 2 NSs to prepare nanocomposites with enhanced conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Except for the organic flame-retardants, various inorganic flame-retardants such as carbon-based materials [25][26][27][28], metal organic frameworks [29,30], silicates [31][32][33][34], black phosphorus [35], graphitic carbon nitride [36], molybdenum disulfide [37,38], have been utilized to enhance the anti-flammability of PLA. Compared to organic flame-retardants, inorganic anti-flammable agents are more efficient in decreasing the heat release and smoke emission at a relatively low dosage.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that the introduction of transition metal (Fe, Ni, Cu, Zn, etc.) compounds into EP can effectively improve its fire safety performance 16–18 . In addition, Sn compounds can reduce CO emissions during the combustion process and weaken the combustion toxicity of polymers 19 .…”
Section: Introductionmentioning
confidence: 99%